2022
DOI: 10.1016/j.jpeds.2021.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum subsp. infantis EVC001 Administration Is Associated with a Significant Reduction in the Incidence of Necrotizing Enterocolitis in Very Low Birth Weight Infants

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Interest in manipulating microbes and their metabolic readouts, including probiotics, prebiotics (that is, substrates for beneficial microbes), synbiotics (microbes and growth stimulants) and postbiotics (microbial metabolites) [93][94][95][96] , as well as FMTs, has since increased considerably. Examples of successful microbiome manipulation in humans includes FMT for Clostridioides difficile infection and the use of probiotics to prevent and treat necrotizing enterocolitis in infants 97,98 .…”
Section: Humansmentioning
confidence: 99%
“…Interest in manipulating microbes and their metabolic readouts, including probiotics, prebiotics (that is, substrates for beneficial microbes), synbiotics (microbes and growth stimulants) and postbiotics (microbial metabolites) [93][94][95][96] , as well as FMTs, has since increased considerably. Examples of successful microbiome manipulation in humans includes FMT for Clostridioides difficile infection and the use of probiotics to prevent and treat necrotizing enterocolitis in infants 97,98 .…”
Section: Humansmentioning
confidence: 99%
“…99.5% of sequences were classified to family-level; only 73.8% were classified to genus-level) – this was largely due to homogeneity within the 16S rRNA gene V4 hypervariable region amongst Enterobacteriaceae . Whilst this was pragmatically necessitated, this depth of differentiation did not reach the level of maximum clinical applicability, when antibiotic choices are based upon species and resistance profiles, and probiotics are formulated at strain level 42 . The capability of shotgun metagenomics to differentiate to these levels has been demonstrated 43-45 and is of the utmost relevance when a clinical future of microbiome manipulation can be envisaged, via the use of narrow-spectrum, targeted antibiotic regimens and probiotic administration.…”
Section: Discussionmentioning
confidence: 99%
“…2 ) 216 . This is important in the context of NEC, as numerous studies have shown that supplementation with Bifidobacterium (and Lactobacillus ) probiotics significantly reduces NEC incidence in preterm infants 217 , including strain EVC001 218 . This links to previous findings in various animal models and ex vivo studies also showing how addition of specific strains of Bifidobacterium can reduce intestinal epithelial cell apoptosis and NEC pathology in vivo 219 .…”
Section: Immune Modulation By Microbiome-based Interventionsmentioning
confidence: 99%